Penerapan Model Pembelajaran Praktikum Berbasis Inquiry Dalam Pembuatan Masker Untuk Meningkatkan Keterampilan Berfikir Kritis, Pemahaman Konsep Dan Psikomotor Siswa - Lena Purnama; Sulistyono Sulistyono; Mulyati Arifin (Edubiologica: Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2018)
Target of this research is to explain influence model study of Inquiry to increase  Skill Of Critical thinking, Understanding of Concept and of Psikomotor Student. Research method the used [is] Mixed Methods Research with desain the used [is] Control post-test pre-test group, namely perceive two selected group. Research Subyek [is] class student of X SMK, while research sampel [is] class student of X counted 71 student ( 2 class). Research instrument in the form of tes ability of critical thinking,understanding of conception and student psikomotor. Before instrument used to be test-drive to know validity, realibilitas, mount distinguishing energy and difficulty, except making of mask [do] not  [to] test-drive. Data collecting [pass/through] pre of tes and of pasca tes. Data analysis [done/conducted] with descriptive analysis and to test hypothesis  [to] test independent t. Before test of statistic, beforehand  [to] test assumption in the form of homogeneity and normalitas. Pursuant to data analysis and solution obtained. : ( 1)Applying of  model study of Inquiry have an effect on to uplifting of skill of critical thinking, understanding of concept and psikomotor [at] cell items [in] class of x SMK. Study executed [in] higher experiment class 27% compared to class of control. Result of improvement ( Gain) of[is understanding of experiment class student concept 0,3 [is] higher the than from class of control. Result of improvement ( Gain) skill of critical thinking [of] experiment class student 0,11 [is] higher the than class of control. : ( 2)Applying of model study of praktikum base on Inquiry can improve the understanding of student concept [at] cell items [in] class of X SMK. . ( 3).Applying of model study of Inquiry can uplift skill critical thinking [of] student [at] cell items [in] class of X SMK. : ( 4)Relation [among/between] variable study of praktikum base on inquiry ably critical thinking and understanding of student concept equal to 15 %.: ( 5)Presentase agreing to usage of model study of Inquiry equal to 79%, while the rest 21% expressing disagree to study of InquiryKeywords: Inquiry; Berpikir Kritis; Pemahaman Konsep; Psikomotor